2011
DOI: 10.1515/hf.2011.141
|View full text |Cite
|
Sign up to set email alerts
|

Recycling potential of unbleached and bleached chemical pulps from juvenile and mature wood ofPopulus deltoides

Abstract: The recycling potential of unbleached and bleached pulps of juvenile and mature wood of poplar (namely ''eastern cottonwood'', Populus deltoides) has been investigated. First, chemical and morphological characteristics of juvenile wood (JW), transition wood, and mature wood (MW) of the trunk were determined. Then, high yield and low yield pulps were produced separately from JW and MW by kraft pulping (KP), followed by bleaching of the low-yield pulp with a DED sequence. The obtained handsheet papers were subje… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 35 publications
(42 reference statements)
0
5
0
Order By: Relevance
“…One of the goals of some selective breeding programs has been to decrease the microfibril angle in the juvenile wood fibers (Courchene et al 2006). Work reported by Hamzeh et al (2012) showed that juvenile wood also can be more susceptible to strength loss upon its use and recycling.…”
Section: Fiber Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…One of the goals of some selective breeding programs has been to decrease the microfibril angle in the juvenile wood fibers (Courchene et al 2006). Work reported by Hamzeh et al (2012) showed that juvenile wood also can be more susceptible to strength loss upon its use and recycling.…”
Section: Fiber Selectionmentioning
confidence: 99%
“…Also, a relatively low pH during drying and a relatively low content of residual hemicellulose tend to make the loss of swellability more severe (Lindström and Carlsson 1982). As shown by Hamzeh et al (2012), fibers from juvenile wood (produced when the tree is younger than a critical age) tend to suffer hornification to a greater degree than mature-wood fibers when subjected to the same conditions of preparation, refining, and papermaking. Jahan (2003) and Sheikhi et al (2010) showed that effects of hornification can be seen in non-wood fibers.…”
Section: Viscoelastic Properties and Creepmentioning
confidence: 99%
“…Even though the use of virgin fibers in this process results in high quality products, alternative use of recycled fibers has important implications in waste management as well as cost and energy savings. However, several drawbacks in such applications need to be considered, such as those associated with the limited strength of the resultant paper products, the presence of more contaminants, and the need to handle sticky particles . Sticky contaminants can enter the process through the raw materials and chemicals additives .…”
Section: Introductionmentioning
confidence: 99%
“…In the case of boxes used to transport perishables goods such as vegetables and fruit, packaging is stored and transported at a low temperature to maintain product quality, but an environment of high relative humidity (RH) is created in the box by the ripening of products during storage and transport. Under these conditions, the performance of packaging is greatly reduced with the increasing moisture content of component papers, resulting in a noticeable loss of compressive strength of packaging 2–5 . As a consequence, corrugated board manufacturers usually over design packaging to reduce the risk of boxes collapsing, incurring higher costs.…”
Section: Introductionmentioning
confidence: 99%
“…Although liner and fluting manufactured from virgin fibres have better compressive performance in high RH environments 4,9 , the use of papers from recycled fibre is growing in the packaging sector. Moreover, it is well known that increasing the number of recycling cycles gradually reduces the strength of recycled paper due to the decreased fibre bond strength caused by the hornification phenomenon 2,10–12 . To solve this problem, papermakers have developed several solutions to improve the strength of recycled papers: (i) modifying the fibrous composition by adding high‐quality fibres; (ii) mechanically refining recycled fibres; (iii) adding dry strength agents to the furnish and, more recently, (iv) adding nanosized celluloses to the pulp suspension at laboratory scale.…”
Section: Introductionmentioning
confidence: 99%